The Splendor of Longing in the Tale of the Genji - Field, Norma, 1947- (Book collections on Project MUSE., 1987)
"Foremost among Japanese literary classics and one of the world's earliest novels, the Tale of Genji was written around the year A.D. 1000 by Murasaki Shikibu, a woman from a declining aristocratic family. For sophistication and insight, Western prose fiction was to wait centuries to rival her work. Norma Field explores the shifting configurations of the Tale, showing how the hero Genji is made and unmade by a series of heroines. Professor Field draws on the riches of both Japanese and Western Scholarship, as well as on her own sensitive reading of the Tale. Included are discussions of the social, psychological, and political dimensions of the aesthetics of this novel, with emphasis on the crucial relationship of erotic and political concerns to prose fictions."--Publisher's description